Do sindicalismo ao ecossocialismo: as lutas dos seringueiros amazônicos como enfrentamento ao modo de sociabilidade capitalista - Matheus Karl Schmidt Schaefer (2022)
From the methodological axis presented by Walter Benjamin, brushing history against the grain, it is proposed to carry out a study through the eyes of predefined historical subjects, in order to present narratives of those who were not the winners in the struggles they have been waging over the years, behold, when not made invisible, they have been criminalized, oppressed and seen as limiting capitalist expansion, capable of influencing the construction and remembrance of experiences, liberations and inspirations for those who are still fighting their fight against barbarism. Since the beginnings of Brazilian colonization, the Amazon has aroused the interests of the local and international bourgeoisie, given the amount and diversity of natural resources still preserved that are functional to capitalist expansion. For years, rubber was an essential raw material for foreign industrial development, with the Amazon region being affected by the overexploitation of the Amazon workforce and natural resources. In this sense, the present research intends to demonstrate the way in which the land concentration and the super-exploitation of work in the extractive reality of Acre were functional for the formation of contemporary capitalism, especially from the 1970s, when integration and colonization of the Amazon region become policies systematized by the dictatorial government aligned with business perspectives. And yet, how the rubber tappers from Acre collectively organized themselves in the face of the extensive and intensive advance of capital in the Amazon, between the 1970s and 1990s. And, to what extent these struggles can contribute to the reflection on the construction of an Ecosocialist Labor Law.